Photodegradation of Atrazine by Ultraviolet Radiation in Different Conditions - narges shamsedini; Mohammad Ali Baghapour; Mansooreh Dehghani; Simin Nasseri (Shiraz University of Medical Sciences, 2015)
Background: Atrazine is one of the most widely used triazine herbicides which has been used for controlling broadleaf and grassy weeds for many years. Its widespread use in water has caused environmental concern because of frequent detection of atrazine in aquatic systems where this herbicide has been spilled. Therefore, the purpose of this study was to determine the herbicide removal efficiency at the optimal conditions. Methods: The effect of different parameters including pH at three different levels (3-11), the initial concentration of atrazine at three different levels (0.1-10 mg/L), and reaction time at five different levels (0-120 min) on the removal of atrazine in the aqueous phase using ultraviolet radiation (1020 μw/cm2) was investigated. Finally, the data were analyzed using SPSS software (version 16). Results: The results demonstrated that atrazine removal rate increased by increasing pH, initial atrazine concentration, and reaction time. The maximum rate of atrazine removal (99.2%) at optimal condition occurred in pH=11, atrazine concentration=10 mg/L at 30 min. Conclusion: According to the findings, it can be concluded that the UV-A process is an effective and commodious method for reducing atrazine in polluted water resources.